Selective Destruction of Interleukin 23–Induced Expansion of a Major Antigen–Specific γδ T-Cell Subset in Patients With Tuberculosis. (26th October 2016) - Shen, Hongbo; Gu, Jin; Xiao, Heping; Liang, Shanshan; Yang, Enzhuo; Yang, Rui; Huang, Dan; Chen, Crystal; Wang, Feifei; Shen, Ling; Chen, Zheng W.
Abstract: A loss of antigen-specific T-cell responses due to defective cytokine signaling during infections has not been reported. We hypothesize that tuberculosis can destroy signaling effects of selective cytokine(s) and induce exhaustion of antigen-specific T cells. To test this hypothesis, mechanistic studies were performed to examine whether and how tuberculosis blocked interleukin 23 (IL-23) and interleukin 2 (IL-2) signaling effects on a major human γδ T-cell subpopulation, phosphoantigen HMBPP–specific Vγ2Vδ2 T cells. IL-23 and IL-2 significantly expanded HMBPP-stimulated Vγ2Vδ2 T cells from subjects with latent tuberculosis infection, and IL-2 synergized the effect of IL-23. IL-23–induced expansion of Vγ2Vδ2 T cells involved STAT3. Surprisingly, patients with tuberculosis exhibited a selective destruction of IL-23–induced expansion of these cells. The tuberculosis-driven destruction of IL-23 signaling coincided with decreases of expression and phosphorylation of STAT3. Interestingly, impairing of STAT3 was linked to marked increases in the microRNAs (miRNAs) hsa-miR-337-3p and hsa-miR-125b-5p in Vγ2Vδ2 T cells from patients with tuberculosis. Downregulation of hsa-miR-337-3p and hsa-miR-125b-5p by miRNA sponges improved IL-23–mediated expansion of Vγ2Vδ2 T cells and restored the ability of these cells to produce anti–tuberculosis cytokines. These results support our hypothesis that tuberculosis can selectively impair a cytokine effect while sparing another and can induce exhaustion of T cells in response to the respective cytokine.